Single choroideremia Gene in Nonmammalian Vertebrates Explains Early Embryonic Lethality of the Zebrafish Model of Choroideremia - Moosajee , M (2017)
PURPOSE. Mutations of the CHM gene underlie the X-linked chorioretinal degeneration choroideremia (CHM). The affected gene product, Rab Escort Protein (REP) 1, mediates the post-translational prenyl modification of Rab GTPases. In patients with CHM, the related REP2 partially compensates for the loss of function of REP1. The objective of this investigation was to study the natural history of disease in a zebrafish model of CHM. METHODS. Zebrafish chm(-/-) were bred and subjected to extensive histologic analysis and TUNEL assays, and cellular extracts were used for immunoblot and in vitro prenylation assays. A detailed evolutionary analysis was performed on the REP family. RESULTS. The retina of chm(-/-) zebrafish develops normally for the first 4 days postfertilization (dpf) but that catastrophic multilayer degeneration synchronous with severe multisystem disease follows. Mean survival time is 4.8 dpf. At the onset of generalized disease, a significant reduction in rep expression levels and activity, with unprenylated rabs accumulating in the cytosol was demonstrated. Extensive bioinformatic analysis of the REP family of proteins revealed a single rep isoform in fish and other nonmammalian vertebrates and invertebrates that is similar to mammalian REP1. CONCLUSIONS. REP1 appears to be the ancestral gene in the family, whereas the intronless REP2 gene is restricted to the mammalian lineage. The results of this study propose that in chm(-/-) zebrafish, maternally derived rep allows initial successful development of the embryo, but its gradual loss leads to multisystem disease and invariably to lethality. In its current form, the chm(-/-) zebrafish has limited usefulness. (Invest Ophthalmol Vis Sci. 2009;50:3009-3016) DOI: 10.1167/iovs.08-2755